DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR PERIODE 2018-2020 - Stella, Stella; Sha, Thio Lie (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine the influence of activity ratio, liquidity, operating leverage and asset growth in manufacturing firm’s capital structure that listed on IDX in 2018-2020 period. The selection sample used purposive sampling method and the valid data were 33 companies. The data is processed with Eviews 12 and Microsoft Excel 2019 program by using multiple regression analysis. The result of this study indicate that asset growth has a significant positive effect on capital structure, while activity ratio, liquidity, and operating leverage have insignificant effect on capital structure. The implication of this research is that a company requires to determine decisions in funding to obtains optimal capital structure so that the company can maintain its existence in the long term.